Perancangan Aplikasi Android Sebagai Pengendali APB (Automatic Patient Bed) dengan Metode Sekuensial (Waterfall) - Mekongga, Ikhthison; Aryanti, Aryanti; Hasan, Yordan (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
Patient beds in hospitals are beds designed for people who need health care. Complaints of hospital nurses are still severe when moving patients from the patient's bed to the operating bed. Therefore we need a tool that can make it easier for nurses to move the patient's body from a particular operating bed to an inpatient bed or vice versa called APB (Automatic Patients Beds). However, the performance of APB (Automatic Patient Beds) that designed is still manual. In this study, android applications developed as controllers of APB (Automatic Patient Beds) with a sequential (waterfall) method, where this application will control the bed so that it can move automatically via android via bluetooth communication. In system design with sequential method consists of several stages, starting from the needs analysis, system design, writing program code, testing, and implementing the program. The results showed that if the patient's bed button clicked, the system would move the mattress to the operating bed, and if the operating bed button were clicked, the mattress would move to the operating bed, the patient's bed would stop if one of the beds were active, This indicates that the mattress has moved to the right position. With this application, it is expected to facilitate patient care in the hospital.